Mathematical Knowledge to Teach Physics and Teacher Training: The case of Kinematics graphs - M. Campos Nava, M.H. Ramírez Díaz, E. Flores Castro, A.A. Torres Rodríguez, L. Morales Maure (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
It is mentioned in the literature that the theoretical construct called Pedagogical Knowledge of Content(CPC) provides methodological elements for the design of teacher training and updating programs. This work presents a proposal for the design of an update course for physics teachers in high school service, in the specific topic of kinematic graphs. The design of this was based on a previous work by the authors, in which they propose to characterize the CPC of the teachers in service, by means of a closed scale Likert test. Based on this instrument, a course consisting of 10 tasks was designed, and where it is promoted in use of two digital tools: GeoGebra and Tracker.